Ramsar convention and convention on biological diversity as mechanism for promoting biodiversity conservation of Malaysia wetlands - Ansari, Abdul Haseeb; Jariah, I; Ibrahim, Irini; Ismail, I (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
The United Nations Convention on Wetlands, the Waterfowl Habitat, 1971, popularly known as the Ramsar Convention, the Convention on Biological Diversity, 1992 (CBD), the Convention on Migratory Birds, the Convention on International Trade on Endangered Species of Wild Fauna and Flora, 1960 (CITES), and International Tropical Timber Agreement (1994) (ITTA) assumes a significant role in wetland conservation worldwide. Wetlands are the ideal habitat for a large variety of plant and animal species that provides for protection of the biodiversity. The Ramsar Convention is an instrument at global level to promote conservation of a particular habitat with the aim of conserving and enhancing wetlands. This convention reflected new international legal efforts aimed at conservation by protecting a habitat type rather than a species, which was the consequence of activities of the non-governmental International Waterfowl Research Bureau. For CBD, which came into force at the United Nations Conference on Environment and Development in Rio de Janeiro, requires Parties to the convention to adopt national strategies, plans or programmes and policies in order to promote the objectives of the convention. Parties must also identify the important components of biodiversity for its conservation, and sustainable use, monitor such components, and categorize activities that are likely to have significant adverse impacts on biodiversity. Both the conventions have pertinent treaty norms which have been given effect through local legislations. Due to the poor enforcement of laws, the objectives of these conventions are yet to be achieved. This paper aims to examine the importance of the two international conventions, and their integrated role in biodiversity conservation of wetlands in Malaysia.